An elastic auto-bone patch for one-step repair large skull defects accompanied by Craniocerebral injury. (September 2020) - Liao, Youguo; He, Qiulin; Zhou, Feifei; Hong, Yi; Wu, Xinyu; Wu, Haoyu; Zhang, Xianzhu; Bunpetch, Varitsara; Zhang, Jingwei; Ye, Guo; Shen, Weiliang; Zhang, Shufang; et al.
Highlights: New strategy of one-step repairing large skull defect with craniocerebral injury. Auto-bone patch composed of bone fragments and hydrogels, promoting bone repair. The elastic auto-bone patch adapted to the change of intracranial pressure. Abstract: Large area skull defects accompanied by craniocerebral injury are life-threating diseases that are difficult to treat due to the large area of damage and intracranial hypertension. An autologous bone is an ideal source for the regeneration of bone, including skull defects. However, two-step treatment, including craniectomy and cranioplasty, is the main strategy in clinical practice to stabilize intracranial pressure, but still remains a huge obstacle in both the preservation of auto-bone fragments and protection of exposed brain tissue. In this study, an elastic auto-bone patch was developed to provide a new and one-step method for repairing large skull defects which are currently repaired with two stages of surgery. The elastic auto-bone patch is formed by bonding auto-bone fragments together using hydrogels, which is then re-implanted to bone defects to repair large skull defects. The auto-bone patch could adapt to changes in intracranial pressure to protect brain tissue for damage, integrate well with surrounding bone tissues, and promote bone regeneration. After 8 weeks implantation, the large-size skull defect is filled with new formed bone tissues in the group of treating with auto-bone patch. This study introduced a new procedure on the application of elastic auto-bone patch to repair large area skull defects. Graphical abstract: Image, graphical abstract